2003
DOI: 10.17305/bjbms.2003.3524
|View full text |Cite
|
Sign up to set email alerts
|

Clomipramine and fluoxetine effects in the treatment of panic disorder

Abstract: Panic disorder (PD) is an acute psychobiologic reaction manifested by intense anxiety and panic attacks, that occur unpredictably with subjective sense of intense apprehension or terror, accompanied by temporary loss of the ability to plan, think, or reason and the intense desire to escape or flee the situation. Panic attacks may last from a few seconds to an hour or longer. Symptoms typically include, among others, palpitations, tachycardia, hypertension, chest pain, dyspnoea, and fear of loosing control or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In studies comparing TCAs and SSRIs, no differences in terms of efficacy were found between the two classes of drugs (Amore et al 1999;Bakish et al 1996;Bakker et al 1999a;Bystritsky et al 1994;Cavaljuga et al 2003;Lecrubier and Judge 1997;Wade et al 1997), with the exception of the tetrayclic antidepressant maprotiline, which had no effect in contrast to fluvoxamine (Den Boer and Westenberg 1988). In most of these studies, the SSRIs were better tolerated than the TCAs, although one analysis did not find a difference in tolerability between SSRIs and imipramine (Otto et al 2001).…”
Section: Comparisons Of Antipanic Drugsmentioning
confidence: 99%
“…In studies comparing TCAs and SSRIs, no differences in terms of efficacy were found between the two classes of drugs (Amore et al 1999;Bakish et al 1996;Bakker et al 1999a;Bystritsky et al 1994;Cavaljuga et al 2003;Lecrubier and Judge 1997;Wade et al 1997), with the exception of the tetrayclic antidepressant maprotiline, which had no effect in contrast to fluvoxamine (Den Boer and Westenberg 1988). In most of these studies, the SSRIs were better tolerated than the TCAs, although one analysis did not find a difference in tolerability between SSRIs and imipramine (Otto et al 2001).…”
Section: Comparisons Of Antipanic Drugsmentioning
confidence: 99%
“…In studies comparing the efficacy of TCAs and SSRIs, no differences in terms of efficacy could be found between the two classes of drugs (Amore et al 1999a;Bakish et al 1996;Bakker et al 1999;Bystritsky et al 1994;Cavaljuga et al 2003;Wade et al 1997), with the exception of maprotiline, which had no effect in contrast to fluvoxamine (den Blaya et al 2007 Yes (C1) 5-HT 3 antagonist ondansetron Schneier et al 1996 Yes (C1) norepinephrine-dopamine reuptake inhibitor bupropion Simon et al 2003 Yes, but not effective in DBPC studies (E) anticonvulsant valproate Primeau et al 1990;Keck et al 1993;Woodman and Noyes 1994 Yes (C1) Selective GABA reuptake inhibitor anticonvulsant tiagabine Zwanzger et al 2001b Yes (C1) Boer and Westenberg 1988). In most of these studies, the SSRIs were better tolerated than the TCAs, although one analysis did not find a difference in tolerability between SSRIs and imipramine (Otto et al 2001).…”
Section: Monoamine Oxidase Inhibitors (Maoi)mentioning
confidence: 99%
“…In depressive patients, 5 mg/day Flx was almost as effective as 20 mg/day, and increase of the dose to 60 mg/day in nonresponders from 20 mg/day brought no additional benefits as compared to continued treatment with 20 mg/day [16]. However, high dose up to 40-80 mg/day Flx showed beneficial effects in other diseases such as obsessive compulsive disorder [17,18], panic attacks [19], eating disorders [20,21] or multiple sclerosis [22,23].…”
Section: Introductionmentioning
confidence: 99%